Successful Treatment of an Elderly Patient With Combined Small Cell Lung Cancer Receiving Anlotinib: A Case Report - Gan, Yuying; Liu, Pingli; Luo, Tao (Frontiers in Oncology, 2021)
Combined small-cell lung cancer (C-SCLC) is a relatively rare subtype of SCLC and is defined by the combination of SCLC and any elements of non-small-cell lung carcinoma. Anlotinib is a novel oral multitarget tyrosine kinase inhibitor that led to significant improvements in progression-free survival and overall survival in third-line therapy of advanced SCLC in the ALTER1202 study. Antiangiogenic therapy with anlotinib in C-SCLC has not previously been reported. An 80-year-old male was admitted with a 20-day history of blood-stained sputum. Chest computed tomography revealed a soft mass (45 × 43 mm) in the right upper lobe, as well as a mediastinal lymph node and additional lung lesions in the homo lung. Pathology confirmed C-SCLC after an ultrasound-guided percutaneous puncture biopsy of the right lung tumor. The elderly patient was given anlotinib monotherapy at a dose of 10 mg/day on days 1–14 of a 21-day cycle after providing informed consent, and the outcome was assessed as continued partial response. As of the last follow-up evaluation, the patient’s progression-free survival was more than 7 months and the treatment showed satisfactory safety. Our findings provide direct evidence of the efficacy of anlotinib in an elderly patient with C-SCLC. More studies are needed to confirm our observations.